A Translation Analysis Of Noun Phrase In Unearthly Novel By Cynthia Hand And Its Translation - Cipto, Desi Titin Rumawati; , Dra. Dwi Haryanti, M. Hum; , Siti Fatimah, S.Pd, M.Hum (2013)
The objectives of this study are (1) to identify the types of category shift found in Unearthly's novel by cynthia Hand and (2) to describe whether the translation of the novel is equivalent or not. The type of this research is descriptive qualitative research. While the object of the study is the Unearthly t novel by Cynthia Hand and its translation. The data of the research are noun phrase that is found in the novel Unearthly by Cynthia Hand. The researcher uses documentation in collecting data and the data were analyzed using comparing method. Based on the analysis, the writer finds the types of translation shift in Unearthly's novel and its translation. They are level shift and structural shift. The level shift divided into 4 types, they are noun phrase which are translated into noun that has 78 data or 41.50 , noun phrase which are translated into verb that has 37 data or 19.70 , noun phrase which are translated into adverb that has 6 data or 3.2% and also noun phrase which are translated into adjective that has 10 data or 5.9%, while structural shift is divided into 3 types noun phrase which are translated into verb phrase that has 26 data or 13.8%, noun phrase which are translated into adverb phrase that has 14 data or 7.4% and also noun phrase which are translated into adjective phrase that has 76 data or 8.5%o. Mostly of the data found by the writer is equivalent translation. From 188 data of translational shift in the novel, 771 data of noun phrase or 9l% belong to equivalent translation and 9o/o or 17 data of noun phrase belong to non-equivalent translation. From the percentages, it can be concluded that the translation of noun phrase in Unearthly's novel and its translation is equivalence.